Thickness measurement of ¹⁰B and ¹¹B targets using the alpha transmission method - D., T.K. Linh; L., X. Chung; L., T. Anh; M., V. Dien; P., D. Khue; N., T. Anh; T., T. Anh; B., T. Hoa; N., T. Nghia; D., T. Tran (Nuclear Science and Technology, 2026)
Experiments were performed to measure the thickness of 10B and 11B targets using the α-transmission method. These targets were prepared at INFN. A 241Am source provided α particles of 5.486 MeV energy. The results were compared with the supplier’s values, showing a good agreement in thickness for the 11B target, while the results for the 10B target were reasonable within the uncertainty range.